Teacher Strategy in Instilling Character Values Through Social Studies Materials in Students of Mts Izharul-Haq Garut - Haprilwanti, Nenden; Sapitri, Wina; Mulyani, Yani; Hasanah, Aan; Arifin, Bambang Samsul (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
Social science is a science whose theories are practiced directly in daily life, in human life there are so-called characters, where every human being has different characters, but there are characters that are in accordance with social life and some that deviate in social life, therefore the teacher as a human being whose duty is to provide guidance and education must be able to apply character values ??to students so that they become human beings who have good character in accordance with existing norms in the community, from this the required appropriate strategies for teachers in instilling character values, one of them by using social studies material in learning. The purpose of this study is to describe how the strategies used by teachers in internalizing character values ??through social studies material in students at Mts Izharul-Haq Garut. From this research it is expected to produce new scientific studies for use in the application of character values ??by teachers using social science materials. So, in addition to being taught the theory students are also equipped with hands-on practice in how to live good character. This research uses qualitative research by using three stages: first, by digging research data at Babat 1 High School, in this case the researcher is a key instrument by interviewing key informants and digging out several documents, the second stage is analyzing the data obtained in the study until finding a conclusion, the next stage of happiness is to check the validity of the data by confirming to the madrasa related to the results of research whether appropriate or not. The results of the research conducted show the conclusions obtained, namely, the teacher is able to apply appropriate strategies in instilling character values ??through social studies material in learning. The role of the teacher in the success of this application is quite significant because the teacher is a person who interacts directly with students in learning and the practice of social science in life so that students will get knowledge as well as direct examples of teachers who teach through the attitudes and actions carried out by the teacher.